Living with paradox: A qualitative study of colorectal cancer patients' experiences in managing their health after cancer treatment. (28th January 2021) - Cuthbert, Colleen A.; Farragher, Janine F.; Farrer, Christie L.; Cheung, Winson Y.
Abstract: Objectives: Managing one's health after colorectal cancer may present specific challenges given long‐term impacts to biopsychosocial functioning. Understanding experiences of managing one's health post‐treatment is important to informing patient‐centred supportive care. Methods: A qualitative study with 19 patients who had completed treatment for colorectal cancer to explore the experience of managing one's health. Following Thorne's Interpretive Description, we conducted interviews using either focus groups or individual interviews. Transcribed data were analysed following Thorne's approach. Sociodemographic and clinical characteristics were also collected. Results: The metaphor of living with paradox was the main theme characterising the experiences of managing one's health in the post‐treatment period. Participants described the ambiguity of health, their need to accept the new normal, losing control and taking back control, experiencing positive and negative life changes, and the need to continually reframe their perspectives to focus on the positives. Conclusion: Our findings suggest that providing patient‐centred care to colorectal cancer survivors post‐treatment involves recognising their changing and sometimes conflicting experiences. Their ability to manage their health may fluctuate and their supportive care needs may not fit with a particular trajectory. Cancer care systems should strive for flexibility in the structure and timing of support available.